Determinan Minat Mahasiswa Mengikuti Brevet Pajak - Muhammad Ainul Yakin; Suyanto Suyanto; Fuadhillah Kirana Putri; Nur Anita Chandra Putry (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to examine the effect of tax knowledge motivation, career motivation, quality motivation, social motivation, economic motivation and achievement motivation on students' interest in taking tax brevets. The samples in this study were obtained from accounting collage students class of 2019-2022 throughout Indonesia by using convenience sampling method. The number of samples used was 221 respondents. This research method use multiple linear regression analysis. The results of the study show that tax knowledge motivation, career motivation, quality motivation and achievement motivation have a positive effect on students' interest in taking tax brevets. Therefore, social motivation and economic motivation have no effect on students' interest in taking tax brevets. This research is expected to provide additional information for tertiary institutions regarding the high interest of students in taking tax brevets. This research is also expected to influence accounting students to take tax brevets so that they can improve their competence in the field of taxation.